Elaboration of Statistics Learning Objects for Mobile Devices - Francisco Javier Tapia Moreno (International Journal of Interactive Mobile Technologies, 2012)
Mobile learning (m-learning) allows a person to study using a mobile computer device anywhere and anytime. In this work we report the elaboration of learning objects for the teaching of introductory statistics using cellular phones.